OP0084 Peg stnf-ri improves health-related quality of life in patients with rheumatoid arthritis. (1st June 2001) - Tesser, JR; Schiff, MH; Davis, MW; Woolley, JM
Abstract : Background: Objectives: To evaluate the effect of PEG sTNF-RI on the health related quality of life (HRQOL) of subjects with rheumatoid arthritis. Methods: In a 12-week, multicenter, randomised, double-blind clinical trial, 194 subjects received either 400- or 800-mcg/kg of PEG sTNF-RI or placebo SC weekly (1:1:1). The study population included subjects with or without background DMARDs (combination therapy involving methotrexate with sulfasalazine or hydroxychloroquine, or sulfasalazine plus hydroxychloroquine). To measure HRQOL, the SF-36 was administered at baseline and at weeks 4 and 12. The SF-36 consists of 36 items designed to assess physical function (PF), role limitations due to physical problems (RP), body pain (BP), general health (GH), vitality/energy (VT), social function (SF), role limitations due to emotional problems (RE), and mental health (MH). The SF-36 is scored from 0 to 100, with higher scores indicating better HRQOL. Differences of 3 to 5 points are considered clinically and socially relevant. The mean change in each SF-36 scale score was compared between subjects receiving PEG sTNF-RI and those on placebo using a repeated measure mixed effect model analysis. The analysis set was a modified intent-to-treat sample, i.e. all patients who received at least one dose were included (n = 193). Results: Subjects using either dose of PEG sTNF-RI experienced statistically significant, and clinically and socially relevant improvements in each SF-36 scale (see Table 1 ). These improvements exceeded those for subjects on placebo in every scale and were statistically significantly improved over placebo for 7 of 8 scales for the 800-mcg/kg dose, and 6 of 8 scales for the 400-mcg/kg dose. Conclusion: Subjects receiving PEG sTNF-RI experienced statistically significant, clinically and socially relevant improvements in their SF-36 scores. These improvements occurred across a full range of health-related quality of life scales, from the physical to the psychosocial, and exceeded those for subjects on placebo. In this population of patients with rheumatoid arthritis, some of whom received DMARD or combination DMARD therapy, PEG sTNF-RI leads to significant and meaningful improvements in health-related quality of life.